2021
DOI: 10.1016/j.addr.2021.113900
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for controlling the innate immune activity of conventional and self-amplifying mRNA therapeutics: Getting the message across

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 243 publications
0
65
0
Order By: Relevance
“…Conventional mRNA has a relatively small size, with 1000–5000 nucleotides [ 21 ], which leads to easier and more effective mRNA encapsulation. Liang et al demonstrated that a conventional mRNA-based vaccine can effectively induce both innate immunity and adaptive responses [ 22 ].…”
Section: Major Types Of Mrna Vaccinementioning
confidence: 99%
“…Conventional mRNA has a relatively small size, with 1000–5000 nucleotides [ 21 ], which leads to easier and more effective mRNA encapsulation. Liang et al demonstrated that a conventional mRNA-based vaccine can effectively induce both innate immunity and adaptive responses [ 22 ].…”
Section: Major Types Of Mrna Vaccinementioning
confidence: 99%
“…Use of base analogues can confer advantages both by ensuring proper protein folding through modulating, as above, production rate and by rendering mRNA invulnerable towards the cell’s innate immune response to foreign mRNAs [ 214 , 227 ]. Cellular recognition of exogenous mRNA is mediated through interaction of the offending molecule with endosomal Toll-like receptors (TLR) 3,7,8 and 12 which leads to its decay, when endogenous mRNA can escape such mechanisms due to the presence of post-translationally modified bases [ 228 ].…”
Section: Mrna Stability and Modificationsmentioning
confidence: 99%
“…The optimal length is a subject of debate; mammalian mRNAs may carry tails comprised of about 250 adenosines but it is considered that tails longer than 150 nucleotides have protruding parts that escape associating with PABPs. “Naked” mRNA poly(A) tails have a propensity to trigger the cytoplasmic deadenylation complex that can compromise mRNA longevity, hence more prudent sizes have been proposed for therapeutic applications [ 159 , 227 ]. A length of 100 to 120 nucleotides is thought to be ideal, increasing translation efficiency and at the same time contributing to uridine depletion by reducing the relative uridine content of mRNA [ 227 , 240 ].…”
Section: Mrna Stability and Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another feature of mRNA as a vaccination tool is its self-adjuvanting property. RNA has been repeatedly reported to curb its own translatability via type I interferon or toll-like receptor (TLR) inducible mechanisms [16][17][18][19][20], thus promoting innate at the expense of adaptive immunity [21,22]. Hence, the use of modified hypoimmunogenic mRNA (e.g., O-methylated cap analogs and chemically modified bases such as pseudouridine) [17], and 5-methyl-cytidine limits the self-adjuvanting property of mRNA enhancing and promotes its translation.…”
Section: Introductionmentioning
confidence: 99%